Paedophilia in Italy: The scale of the problem, ethical aspects and protection of minors - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2018)
In recent years, society has been dealing with the rapid development of the global scourge of the sexual exploitation of children, which, according to some findings, has become a new form of slavery. On the one hand, various social initiatives are being launched in many countries with the main goal of combating the sexual exploitation of minors; on the other, the Internet and other modern information technologies give paedophiles new opportunities to interact with children in the virtual world or distribute paedo-pornographic materials. Italy is one of the many countries in which paedophilia has recently become a subject of intense public interest. The main objectives of this article are to outline the causes and specificities of the sexual exploitation of children in Italy and to explore the most important ethical aspects of this phenomenon.